2013
DOI: 10.1038/onc.2012.598
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-mediated silencing of the miR-124 genes facilitates pancreatic cancer progression and metastasis by targeting Rac1

Abstract: Previous studies have demonstrated that microRNA (miRNA) expression is altered in human cancer. However, the molecular mechanism underlying these changes in miRNA expression remains unclear. In this study, we investigated the epigenetic modification of miR-124 genes and the potential function of miR-124 in pancreatic cancer. Using pyrosequencing analysis, we found that miR-124 genes (including miR-124-1, miR-124-2 and miR-124-3) are highly methylated in pancreatic cancer tissues compared with in non-cancerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 46 publications
7
163
1
Order By: Relevance
“…The Table 3. Changes in miRNAs in superior mesenteric arteries after hypoxia effects of the mutant 3=-UTR control of RhoA and Rac1 were also investigated in this experiment (22).…”
Section: Mechanism Of Mir-124/mir-141 Regulation Of Rhoa and Rac1 Efmentioning
confidence: 99%
“…The Table 3. Changes in miRNAs in superior mesenteric arteries after hypoxia effects of the mutant 3=-UTR control of RhoA and Rac1 were also investigated in this experiment (22).…”
Section: Mechanism Of Mir-124/mir-141 Regulation Of Rhoa and Rac1 Efmentioning
confidence: 99%
“…97 Hypermethylation mediates the silencing of miR-124, thereby promoting pancreatic cancer metastasis. 126,127 Downregulation of miR-212 due to promoter hypermethylation promotes EMT as well as cell migration and invasion in vitro and promotes the formation of intrahepatic and pulmonary colorectal cancer metastasis in vivo. 128 In contrast, miR-135b, which promotes NSCLC metastasis in vivo, is regulated by DNA demethylation.…”
Section: Biomarkers For Cancer Prognosismentioning
confidence: 99%
“…23,[28][29][30] Interestingly, some studies have shown that miR-124 directly controls Rac1 expression by binding to the 3 0 -UTR of Rac1 mRNA. 40,41 MicroRNA-124 acts as a tumor suppressor in MG-63 and U2OS The soluble TNF-a release and TNF-a mRNA were inhibited by overexpression of miR-124. In contrast, the ectopic expression of mutated 3 0 -UTR Rac1 significantly abrogated the effect of downregulated TNF-a production induced by miR-124.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, miR-124 also inhibits cell proliferation, invasion, and metastasis by directly controlling Rac1 in pancreatic cancer. 41 Therefore, to investigate the possible mechanism through which miRNAs are involved in the inflammatory action of AGA, the expression of miRNAs that have been found to either regulate Rac1 expression or undergo inflammatory response was examined by qRT-PCR. We found that miR-124 expression decreased by nearly 5-fold in the presence of AGA, whereas the levels of other miRNAs were not affected.…”
Section: Discussionmentioning
confidence: 99%